A QUALITATIVE ANALYSIS OF MICROTRANSACTION AND CONSUMER BEHAVIOR OF ONLINE GAMES (CASE STUDY: PUBG MOBILE GAMES) - Ridho Prawira Ramadhanu; Frederik G. Worang; Shinta J. C. Wangke (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
In terms of gaming especially related to Micro transaction, people tend to spend money in order to do micro transactions to fulfill their needs and wants within the game. The game's needs and wants are usually related to winning a particular match, getting the limited type of outfits, bragging rights with other players, and more. The purpose of this study is to see the relation of micro transaction with the consumer’s behavior related to the needs and wants within the game, in this case, PUBG Mobile Games. This study uses a qualitative method and interviews with informants were conducted in order to gain information regarding the phenomenon. The finding of this study shows there is a major connection between micro transaction and consumer behavior, which is about the hedonistic traits, the existence of micro transaction makes people or players of the game have more hedonistic judgment and traits during the transaction Based on the result, the researcher provided several recommendations which are considerations regarding the level of importance in using micro transaction and the utilization on a large scale and improvement of the micro transaction need to be done in order to gain more users by the company Keywords: micro transaction, online games.